Spatial optimization of the food, energy, and water nexus: A life cycle assessment-based approach. (August 2018) - Yuan, Kuang-Yu; Lin, Ying-Chen; Chiueh, Pei-Te; Lo, Shang-Lien
Abstract: Since the Bonn 2011 Conference, the Food-Energy-Water (FEW) nexus has become one of the most popular global research topics. Understanding and addressing the complex interactions between the FEW components is essential for sustainable development. This study proposes an environmental impact minimization model, which considers the FEW nexus under four climate change scenarios, to optimize the spatial distribution of three energy crops (rice, corn, and sugarcane). Life cycle assessment (LCA), linear programming, and a climate change simulation model are integrated to analyze appropriate bioenergy production rates while comparing the benefits of bioenergy with the current renewable energy policy in Taiwan. The major findings of LCA in this study indicate that electricity generation using bio-coal produced from rice straw is very beneficial to the environment. Considering the spatial characteristics of Taiwan, simulations from the spatial optimization model suggested that (a) the rice and corn cultivation areas should be increased in southern Taiwan for bio-coal and bioethanol production, in accordance with the "food and feed priority policy"; and (b) the rice cultivation area should be decreased across Taiwan, based on the "water conservation policy". In addition, compared to solar power, the development of bioenergy can simultaneously enhance food and energy self-sufficiency. Graphical abstract: fx1 Highlights: A useful FEW framework was established using the proposed integrated approach. FEW nexus policy scenarios are applied to evaluate the environmental performance. Increased bioenergy crop production in southern Taiwan under the food scenario. Decreased area of rice cultivation across Taiwan under the water scenario. Spatial optimization is helpful for proper management of bioenergy policies.